2013
DOI: 10.1002/app.39470
|View full text |Cite
|
Sign up to set email alerts
|

Cationic starch for microalgae and total phosphorus removal from wastewater

Abstract: The city of Logan, Utah treats wastewater in 460 acres of facultative lagoons. Naturally growing algae in these lagoons uptake nutrients and remediate the wastewater, but require coagulation and flocculation for separation from wastewater. Cationic corn starch and cationic potato starch with a degree of substitution 1.34 and 0.82, respectively, were synthesized using 3-methacryloyl amino propyl trimethyl ammonium chloride and tested on Scenedesmus obliquus and lagoon wastewater. The zeta potential of the catio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Anthony and Sims (2013) find that cationic starch can effectively flocculate algae cells and remove total phosphorus in wastewater with an upward trend of TP removal with increasing dosage. Cationic starches serve as substrates in anaerobic digestion or fermentation processes using the harvested biomass as feedstock and such biomass can be safely used as animal feed or fertilizer (Anthony and Sims, 2013). Cationic starch modified soil has been reported by Shi et al (2016) as the effective algae flocculant with the loading of 0.11 g/L for a removal efficiency of 86%.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anthony and Sims (2013) find that cationic starch can effectively flocculate algae cells and remove total phosphorus in wastewater with an upward trend of TP removal with increasing dosage. Cationic starches serve as substrates in anaerobic digestion or fermentation processes using the harvested biomass as feedstock and such biomass can be safely used as animal feed or fertilizer (Anthony and Sims, 2013). Cationic starch modified soil has been reported by Shi et al (2016) as the effective algae flocculant with the loading of 0.11 g/L for a removal efficiency of 86%.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the HABs removal using clays, chitosan is used to modify the local soils and applied to small natural waters to control both cyanobacteria blooms and sediment nutrient release, leading to recovery in submerged macrophytes Pan, 2015, 2013;Pan et al, 2012). Anthony and Sims (2013) find that cationic starch can effectively flocculate algae cells and remove total phosphorus in wastewater with an upward trend of TP removal with increasing dosage. Cationic starches serve as substrates in anaerobic digestion or fermentation processes using the harvested biomass as feedstock and such biomass can be safely used as animal feed or fertilizer (Anthony and Sims, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Turbidity of the water was measured at 890 NTU (Hach 2100Q turbidimeter). Algae biomass inoculum for the laboratory RABRs was collected from the pilot scale RABR systems currently operating at the Logan City wastewater treatment facility, a 460 acre (1.86 km 2 ) open lagoons system [19]. Visual microscopy of the pilot scale RABR based biofilm indicated that the collected algae biomass contained a variety of algae species, with Pseudanabaena , Oscillatoria , and Chroococcus as the predominant species.…”
Section: Methodsmentioning
confidence: 99%
“…To achieve sustainability in microalgae harvesting, organic coagulants must be tested and utilized. Organic coagulants such as cationic starch, chitosan, and guar gum have been to a certain extent researched for microalgae harvesting [9,[11][12][13]. Organic coagulants are naturally available, inexpensive, and can provide a source of carbon for downstream processes such as in fermentation or anaerobic digestion of the harvested biomass.…”
Section: Desalination and Water Treatmentmentioning
confidence: 99%